A systematic approach for data validation using data-driven visualisations and interactive reporting - Jules Zaccardi; Enrico Infante (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2021)
In this article we present the development of a tool that can serve most official statistics. This tool is fully interactive and based mostly on visualisations, which makes it a powerful ally to validate or analyse data. To make our tool a pragmatic solution in an era facing ever larger volumes of data, we integrated a data-driven analysis to identify the most unusual data and suggest them to the user. By defining the right metrics and smartly designing our report, we managed to develop an easily-accessible tool that can be used to validate or analyse data. We tested this tool for data validation in annual financial accounts, and it demonstrated its ability to identify the main issues in the dataset very quickly, therefore improving i) the productivity of the user of the tool ii) the long-term viability of the validation and iii) ultimately the quality of the data.
Keywords: C02; C61; G20; P43; 330; data literacy; data validation; automation; visualisation; design; outlier detection